2017
DOI: 10.1159/000486317
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Piezoelectric Sensor Array-Based Device for Measurement of Carotid-Femoral Pulse Wave Velocity: The Philips Prototype

Abstract: Background: Multiple piezoelectric pressure mechanotransducers topologized into an array might improve efficiency and accuracy in collecting arterial pressure waveforms for measurement of pulse wave velocity (PWV). Objective: In the present study, we validated a piezoelectric sensor array-based prototype (Philips) against the validated and clinically widely used Complior device (Alam Medical). Methods: We recruited 33 subjects with a wide distribution of PWV. For the validation, PWV was measured sequentially w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Previous studies using piezo-based sensors have been able to reliably detect PWs in healthy volunteers [ 25 , 26 ], volunteers with arrythmias [ 23 ], and hypertensive patients [ 12 ]. In a recent study, the use of novel piezoelectric sensors resulted in a PW detection rate of 98% from the radial artery [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using piezo-based sensors have been able to reliably detect PWs in healthy volunteers [ 25 , 26 ], volunteers with arrythmias [ 23 ], and hypertensive patients [ 12 ]. In a recent study, the use of novel piezoelectric sensors resulted in a PW detection rate of 98% from the radial artery [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This pulse system was found to be effective compared with previous pulse acquisition platforms. Xu et al [ 21 ] confirmed that a piezoelectric sensor array-based device had similar accuracy and reproducibility for measuring the pulse wave velocity (PWV). Park et al [ 22 ] described a stretchable array of highly sensitive pressure sensors that consisted of polyaniline nanofibres and Au-coated polydimethylsiloxane micropillars that exhibited great potential in wearable devices.…”
Section: Discussionmentioning
confidence: 99%
“…This pulse system was demonstrated effectiveness than previous pulse acquisition platforms. Xu et al [19] validated that a piezoelectric sensor array-based device had similar accuracy and reproducibility in measuring pulse wave velocity (PWV). Park et al [20] reported a stretchable array of highly sensitive pressure sensors consisting of polyaniline nanofibers and au-coated polydimethylsiloxane micropillars, which showed great potential in wearable device.…”
Section: Discussionmentioning
confidence: 99%